2021
DOI: 10.3389/fphar.2021.634016
|View full text |Cite
|
Sign up to set email alerts
|

The Extent and Impact of Variation in ADME Genes in Sub-Saharan African Populations

Abstract: Introduction: Investigating variation in genes involved in the absorption, distribution, metabolism, and excretion (ADME) of drugs are key to characterizing pharmacogenomic (PGx) relationships. ADME gene variation is relatively well characterized in European and Asian populations, but data from African populations are under-studied—which has implications for drug safety and effective use in Africa.Results: We identified significant ADME gene variation in African populations using data from 458 high-coverage wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…Our study found that cytochrome P450 ( CYP540 ) genes harbor many rare variants in agreement with previous reports ( Fujikura et al, 2015 ; Wright et al, 2018 ; Tasa et al, 2019 ; da Rocha et al, 2021 ). Considering that approximately 79% of widely used drugs are metabolized by enzymes of the CYP450 family, the impact of rare variants potentially related to the generation of ADRs in the sampled population is significant ( Phillips et al, 2001 ; Zanger and Schwab, 2013 ; Fujikura et al, 2015 ; Tornio and Backman, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that cytochrome P450 ( CYP540 ) genes harbor many rare variants in agreement with previous reports ( Fujikura et al, 2015 ; Wright et al, 2018 ; Tasa et al, 2019 ; da Rocha et al, 2021 ). Considering that approximately 79% of widely used drugs are metabolized by enzymes of the CYP450 family, the impact of rare variants potentially related to the generation of ADRs in the sampled population is significant ( Phillips et al, 2001 ; Zanger and Schwab, 2013 ; Fujikura et al, 2015 ; Tornio and Backman, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Recent advances in genomics have illustrated the rich genetic diversity of African populations [4,5] and its associated health implications, such as varying lipid profiles [6], predisposition to kidney disease [7] and more [8]. Similar diversity has been observed in pharmacogenomics studies, where, for example, population-specific alleles and frequencies have been found in the genes encoding the cytochrome P450 (CYP) enzymes in Africans, together with structural variants that impact enzymes functionality [9][10][11].…”
Section: Introductionmentioning
confidence: 74%
“…SNVs and star alleles, stored in the 'Variant' table, provide information about the variants, and these are associated with phenotypes, which could be related to either the response to a drug or a disease. The star allele variants from PharmGKB were retrieved to account for the particularity of annotating the absorption distribution metabolism excretion (ADME) genes [10]. Note, that a star allele is defined by a set of core variants that define the phenotype associated with the drug response in linkage disequilibrium with other variants, of which presence or absence is not necessarily related to the drug-response phenotype [17][18][19].…”
Section: Agmp Data Model and Contentmentioning
confidence: 99%
“…Its occurrence among genetically diverse groups (reflected in self-identify) in South Africa has been shown to vary significantly even among geographically neighboring populations [3]. Moreover, clinically actionable variants of ADME genes deviate significantly between Sub-Saharan Africa and other worldwide populations [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, these variants cannot solely explain the wide range of observed drug-response phenotypes [8]. In particular, rare variants were shown to have an important share of the genetic makeup and were identified for their putative functional implication in ADME genes [5,7,9,10]. The important status of rare variants has been also highlighted recently as critical to consider in deriving personalized medicine strategies [11].…”
Section: Introductionmentioning
confidence: 99%